2018
DOI: 10.1002/sia.6590
|View full text |Cite
|
Sign up to set email alerts
|

Bulk synthesis of linear carbon chains confined inside single‐wall carbon nanotubes by vacuum discharge

Abstract: Carbyne, an infinite carbon chain, has attracted much interest and induced significant controversy for many decades. Recently, the presence of linear carbon chains (LCCs), which were confined stably inside double‐wall carbon nanotubes (DWCNTs) and multiwall carbon nanotubes (MWCNTs), has been reported. In this study, we present a novel method to produce LCCs in a film of carbon nanotubes (CNTs). Our transmission electron microscopy and Raman spectroscopy revealed the formation of a bulk amount of LCCs after el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
(36 reference statements)
5
15
0
Order By: Relevance
“…Long linear carbon chains encapsulated in MWCNTs and DWCNTs have been reported previously [37][38][39][40][41][42][43][44][45]. In the present study, carbon chains encapsulated not only in DWCNTs but also in SWCNTs were observed, as previously reported [46]. Figure 6 shows two SWCNTs encapsulating carbon chains.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Long linear carbon chains encapsulated in MWCNTs and DWCNTs have been reported previously [37][38][39][40][41][42][43][44][45]. In the present study, carbon chains encapsulated not only in DWCNTs but also in SWCNTs were observed, as previously reported [46]. Figure 6 shows two SWCNTs encapsulating carbon chains.…”
Section: Resultssupporting
confidence: 90%
“…Recently, we have found out the presence of long linear carbon chains after electrical discharge during field electron emission from single-wall carbon nanotube (SWCNT) films [46], which is different from the previous method by arc discharge and high-temperature heat treatment. The present reproducible synthesis method may provide a new approach to the bulk production of long linear carbon chains.…”
Section: Introductionmentioning
confidence: 73%
“…5(a-c)) of the CNTs synthesized in the presence of a 2 % Ni/4 % Y wt. mixture revealed that the CNTs have a great number of layers and are therefore properly described as multiple-wall carbon nanotubes (MWCNTs) with amorphous carbon particles attached to the surface of the nanotubes; this morphology was previously observed in other works [9,38]. Carbon nanoparticles confined inside CNTs by the effect of the arc discharge were also detected and informed previously in other work [38].…”
Section: Study Of the Morphology Of Cnts Using Sem And Temsupporting
confidence: 73%
“…A thick film of eDIPS SWCNT (Meijo Nano Carbon) was used as an FE cathode, and an anode made of a tungsten grid was placed in front of the SWCNT cathode with a separation of about 1.6 mm in a high vacuum of 10 −6 Pa. Details of the FE set-up for the production of LCC@CNT have been described in our previous reports [16,17]. When an excessive voltage was applied between the electrodes, a spark discharge occurred.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter physical method, 1D carbon chains were obtained as by-products of multiwall CNTs. We discovered a novel method to produce long LCCs encapsulated inside single-wall CNTs (SWCNTs) on a film scale after field emission (FE) experiments of the CNT film cathode, as reported in the previous ALC '17 [16].…”
Section: The Electronic Energy Gap Of Hydrogen-capped Polyynesmentioning
confidence: 96%